Demokrasi dan Kinerja Pers Indonesia - Ngurah Putra, I Gusti (Jurnal Ilmu Komunikasi, 2006)
Abstract: Mass media, especially, press have important rules in the democration process. There are three criteria to evaluate performance of the press. Press as a civic forum, itâs related to Habermasâs public sphere that there is space for citizen to discuss about public interest inÂ the free condition. Press as a watch-dog, that itâs means press has to protec minority rights from malfuntion of majority power. Press as a mobilization agent, itâs medium to increase society involment in the politic process.